Deep Stories Practicing, Teaching, and Learning Anthropology with Digital Storytelling - Nuñez-Janes, Mariela (Walter de Gruyter, Inc., 2017)
Have you ever wondered what makes storytelling and digital media a powerful combination? This edited volume examines the opportunities to think, do, and/or create jointly afforded by digital storytelling. The editors of this volume contend that digital storytelling and digital media can create spaces of empowerment and transformation by facilitating multiple kinds of border crossings and convergences involving groups of peoples, places, knowledge, methodologies, and teaching pedagogies. The book is unique in its inclusion of anthropologists and education practitioners and its emphasis on multiple subfields in anthropology. The contributors discuss digital storytelling in the context of educational programs, teaching anthropology, and ethnographic research involving a variety of populations and subjects that will appeal to researchers and practitioners engaged with qualitative methods and pedagogies that rely on media technology.